2014
DOI: 10.3109/10717544.2014.917388
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release effervescent buccal discs of buspirone hydrochloride:in vitroandin vivoevaluation studies

Abstract: In the present study controlled release effervescent buccal discs of buspirone hydrochloride (BS) were designed using HPMC as rate controlling and bioadhesive polymer by direct compression method. Sodium bicarbonate and citric acid were used in varying amounts as effervescence forming agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…Mucoadhesive strength of tablets was determined by using a texture analyzer (Middleboro, MA, USA). 20 , 26 Fresh buccal mucosa from the sheep obtained from local slaughterhouse was used as a model membrane. Samples were prepared by separating the underlying adipose tissue, and the obtained mucosal membrane was cut into 2×2 cm pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Mucoadhesive strength of tablets was determined by using a texture analyzer (Middleboro, MA, USA). 20 , 26 Fresh buccal mucosa from the sheep obtained from local slaughterhouse was used as a model membrane. Samples were prepared by separating the underlying adipose tissue, and the obtained mucosal membrane was cut into 2×2 cm pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Jaipal et al showed that the carbon dioxide released from buccal effervescent discs upon contact with saliva acts as a permeation enhancer (compared to noneffervescent discs) (61). Although this is an attractive alternative for pediatric patients due to the increased bioavailability effect, further investigations are required to assess the safety of this dosage form.…”
Section: Effervescent Buccal Discsmentioning
confidence: 98%
“…Effervescent tablets (ETs) can quickly disintegrate because of the gas-generating reaction of an acidic agent (e.g., citric acid) and an alkaline agent (e.g., sodium bicarbonate) when coming into contact with water, therefore accelerating the release and improving the bioavailability of the included drugs. 1,2 However, certain drawbacks (e.g., frequent sticking, high hygroscopicity, and low hardness) of the ETs limit their practical production and applications. In particular, sticking can frequently occur in the tableting process due to the ease with which the acidic agent adheres onto the punch tips of the tablets during compaction.…”
Section: Introductionmentioning
confidence: 99%